Forças evolutivas atuando sobre o gene RH1 em ciclídeos neotropicais com diferentes dietas. - Stabile, Bruno Henrique Mioto (2021)
Neotropical aquatic environments are highly heterogeneous and present a broad light spectral variation. Photic conditions can be closely related to aquatic vertebrates’ visual system evolution, which can interfere with ecological factors, such as feeding. Therefore, due to the species’ biodiversity and ecological adaptations observed in continental aquatic environments, Neotropical cichlids represent an important model for evolutionary studies. Cichlinae shows several adaptations regarding their life cycle and may present and accumulate mutations resulting in specific amino acid changes of visual proteins. These proteins are encoded by visual opsins genes, which allow some “measurement” of natural selection on the protein using molecular tools. Thus, it is possible to verify whether the diet constitutes an important factor in the diversification of the gene responsible for the scotopic vision of these vertebrates. In this study, 40 species of Neotropical cichlids were categorized according to their diet and, using different codon selection analyses, different protein sites positively selected were observed in specialist and generalist species. The lineages of predatory fish showed evidence of a stronger evolution of the RH1 gene when compared to other groups, indicating the influence of the diet on this group's visual evolution.